Characterization, Simulation and Optimization of Surface Etched Slotted Tunable Laser Diodes - WALLACE, MICHAEL JAMES (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
The past decades have seen near exponential growth in internet traffic. To meet this growth, optical communication networks continue to branch deeper into network architectures, replacing electrical based communication. In order to reduce deployment costs of such expansive networks, low-cost optical components integrated at ever-increasing densities are needed. Semiconductor laser diodes represent an indispensable optical component in such networks with significant research being undertaken to reduce their cost and complexity. Such laser diodes are sensitive to thermal fluctuations and with increasing component density this thermal behaviour becomes an important factor. Previous research in the Trinity College Dublin semiconductor photonics group has yielded a low-cost laser diode design based on surface etched slotted gratings. The research presented in this thesis focuses on developing a detailed understanding of the dynamics of these lasers. This is undertaken through a combination of experimental characterisation and the development of a thermo-optic model capable of simulating 3-D thermal distributions as well as a variety of both transient and static optical properties. The thermo-optic model is verified through a range of experimental measurements, including the use of surface temperature maps acquired using the CCD-TR technique, showing excellent agreement and predictive capabilities. The improved understanding of the thermal dynamics of the lasers is applied in the form of an athermal tuning scheme achieving wavelength stability of ?0.01 nm over a temperature range of 10 ◦C to 85 ◦C. Finally, a genetic algorithm is developed, leveraging the aforementioned model to optimize the slotted laser diodes with a high degree of accuracy. Previous designs are re-optimized, improving both slope efficiency and thermal tolerances, and new designs are generated for low linewidth and direct modulation applications.
APPROVED
Keywords: Semiconductor lasers; Tunable semiconductor lasers; Laser theory; Distributed Bragg reflectors; Slotted gratings; CCD thermoreflectance; Thermal mapping; Thermoreflectance spectroscopy; Thermo-optical modeling; Integrated optics; Finite element method; Time domain transfer matrix method; Genitic algorithm; Athermal lasers; Scattering matrix method